Stick-slip chaos in a non-ideal self-excited system - Pontes, B. R. [UNESP]; Balthazar, José Manoel [UNESP]; Oliveira, V. A. (ASME International, 2003)
In engineering practical systems the excitation source is generally dependent on the system dynamic structure. In this paper we analyze a self-excited oscillating system due to dry friction which interacts with an energy source of limited power supply (non ideal problem). The mechanical system consists of an oscillating system sliding on a moving belt driven by a limited power supply. In the oscillating system considered here, dry friction acts as an excitation mechanism for stick-slip oscillations. The stick-slip chaotic oscillations are investigated because the knowledge of their dynamic characteristics is an important step in system design and control. Many engineering systems present stick-slip chaotic oscillations such as machine tools, oil well drillstrings, car brakes and others.
Keywords: DC motors; Elastic moduli; Friction; Machine tools; Nonlinear systems; Oscillations; Systems analysis; Self-excited systems; Stick-slip chaos; Chaos theory